REALISASI PENGGUNAAN DANA DESA DALAM MENGEMBANGKAN PEREKONOMIAN MASYARAKAT DI DESA TAMANSARI KECAMATAN SUMBERMALANG KABUPATEN SITUBONDO JAWA TIMUR - Gufron, Moh Idil; Arifin, Indana Fitriyatul; Sonia, Siti Ibra (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2021)
The Village Fund is prioritized to finance the implementation of local village-scale programs and activities in the field of village development such as housing facilities and infrastructure, food security, health, education and to finance the field of community empowerment, namely programs aimed at increasing the capacity of rural communities in entrepreneurial development, increasing income, and expansion of the economic scale of individual citizens or community groups. After the village fund, the community began to feel a positive impact as seen from the collaboration between the government and the community in increasing the development of village facilities and infrastructure such as community economic activities aimed at improving the economy of the Tamansari village community. The research uses an ethnographic approach, because initially this method was mostly used for research in the field of cultural anthropology. The type of research used by researchers is qualitative research. The economic development of the Tamansari Village community before the existence of village funds has not been able to be felt by the community as a whole.